Entrepreneurship research amid transitional economies: domains and opportunities. Issue 2 (1st June 2015) - Song Lin, Prof. Philippe Lasserre, Prof.; Lin, Song; Lasserre, Philippe
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This special issue of Chinese Management Studies aims to focus on entrepreneurship in China by addressing a variety of topics. The purpose is to provide some insights for entrepreneurship research based on the context of China as a representative emerging economy. Design/methodology/approach – Review and reflection. Findings – The research presented in the eight articles that constitute this special issue concern different topics, including entrepreneurship in the Chinese historical context, entrepreneurship in the context of networks and relationships and entrepreneurship in specialized industries. These articles provide valuable contributions to theory construction in entrepreneurship research for emerging economies, not just for enterprises in China but also for people and ventures around the world. Research limitations/implications – Developing an indigenous understanding of the opportunity for entrepreneurship research in an emerging economy such as China, we would argue, is only the beginning for the research work based on the historical context, networks and relationships, and specialized industries that could boom in the wide open workspaces of the developing world. Originality/value – The studies published here provide valuable contributions to theory construction in entrepreneurship research, as well as some basic ideas for concept definition and structural comparison in entrepreneurship research in other different domains.